Optimization of PETG 3D printing parameters for the design and development of biocompatible bone implants - Sultan, M. Moeen; Aized, Tauseef; Farooq, M.; Anwar, Saqib; Ahmad, Naseer; Tauseef, Ambreen; Riaz, Fahid (Frontiers in Bioengineering and Biotechnology, 2025)
The search for suitable manufacturing methods and the selection of biocompatible material with good mechanical properties is still a major challenge in implant development. polyethylene terephthalate glycol (PETG) is a thermoplastic extensively utilized in biomedical applications, like tissue engineering, dental, scaffolds and surgery, because of its biocompatibility. Fused deposition modeling (FDM) is gaining importance in wide range of applications for developing custom shaped medical implants. This study aimed to fabricate a cranial implant using the optimized parameters of 3D printed PETG for good mechanical properties. The research investigates the optimization of key printing parameters like layer height, line width and print speed for PETG material by utilizing Box Behnken Design (BBD). Analysis suggests that the influential parameters of FDM are layer height and line width, which significantly influence tensile and compressive strength. The analysis of variance (ANOVA) showed that a layer height of 0.12 mm, line width of 0.77 mm and print speed of 25.75 mm/s indicated the increased value of tensile and compressive strength, i.e., 51.18 MPa and 52.33 MPa, respectively. The effectiveness of the RSM model was confirmed using the validation experiment, with errors less than 2%. Additionally, this study presents the process framework for the development of customized cranial implants by using computed tomography (CT) scan data of the patient. The 3D printed implant tested under uniaxial compressive load shows an average peak value of 1088 N. The goal of this research is to assist surgeons in overcoming clinical challenges faced while selecting materials and in-house production of patient-specific implants. A further evaluation of the presented technology is recommended for its potential use in clinical trials.